MUSIC THERAPY - AN INNOVATION: संगीत चिकित्सा -एक नवाचार - Tiwari, Premlata (International Journal of Research -GRANTHAALAYAH, 2015)
This music descends from the middle of the vocal waves to the ears and makes a place in the heart. Dropping of drops, rustling of leaves, rippling of waves, tweeting of birds is the only music that cannot be denied when a Karna beloved music resonates, there is not only vibration in the heart, but the musical colors It dissolves the mind by dissolving in it. Osho had said that one thing should be saved in life and that is the soul and its music because the brain and heart stand on the ground of music and merge into each other. How many arguments, how many beliefs, how many definitions, how many opinions, how many theories but music is equally impassable, unknown and intense. Yes, Rigveda says: यह संगीत स्वर लहरियांे के मध्यम से कानों में उतरकर दिल में जगह बनाता है। बूंदांे का टपकना, पत्तों का सरसराना, लहरांे का लहराना, पंछियांे का कलरव करना संगीत ही तो है इस बात से इंकार नहीं किया जा सकता कि जब कोई कर्ण प्रिय संगीत की लहरियाँ गूंजती है तो हदय में न केवल कंपन होता है,बल्कि संगीत रंगों में घुलमिलकर मन को अमृतमय कर देता है। ओशो ने कहा था कि जीवन में एक ही चीज बचानी चाहिए और वह है आत्मा और उसका संगीत क्योकि मस्तिष्क और हृदय संगीत की धरातल पर ही खडे़ होकर एक दूसरे मे लीन हो जाते हैं। कितने तर्क,कितने विश्वास,कितनी परिभाषाएँ, कितने मत,कितने सिद्धांत लेकिन संगीत उतना ही अगम्य, अज्ञात और गहन है। ़ ़ऋग्वेद कहता हैः